2020
DOI: 10.1523/jneurosci.1458-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

The VGF-derived Peptide TLQP21 Impairs Purinergic Control of Chemotaxis and Phagocytosis in Mouse Microglia

Abstract: Microglial cells are considered as sensors of brain pathology by detecting any sign of brain lesions, infections, or dysfunction and can influence the onset and progression of neurological diseases. They are capable of sensing their neuronal environment via many different signaling molecules, such as neurotransmitters, neurohormones and neuropeptides. The neuropeptide VGF has been associated with many metabolic and neurological disorders. TLQP21 is a VGF-derived peptide and has been shown to signal via C3aR1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 59 publications
3
29
0
Order By: Relevance
“…Indeed, the data presented here are consistent with causal roles for TLQP-62 and the VGF proprotein in AD pathogenesis and progression, but do not rule out contributions of other VGF-derived peptides including TLQP-21, an activator of the C3aR1 complement receptor 66 . Of note, we and others have recently shown that TLQP-21 reduces neuropathology in male 5xFAD mice and increases amyloid uptake in transformed BV2 mouse microglia and in primary cultured mouse microglia via a C3aR1-dependent pathway [87][88][89] , consistent with the previous identification of a critical complement network module in AD 5 .…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, the data presented here are consistent with causal roles for TLQP-62 and the VGF proprotein in AD pathogenesis and progression, but do not rule out contributions of other VGF-derived peptides including TLQP-21, an activator of the C3aR1 complement receptor 66 . Of note, we and others have recently shown that TLQP-21 reduces neuropathology in male 5xFAD mice and increases amyloid uptake in transformed BV2 mouse microglia and in primary cultured mouse microglia via a C3aR1-dependent pathway [87][88][89] , consistent with the previous identification of a critical complement network module in AD 5 .…”
Section: Discussionsupporting
confidence: 91%
“…Mice that lack MER and AXL specifically in microglia accumulate neuronal progenitor cells in the subventricular zone, and this phagocytotic process seems to driven by TAM receptor ligands Gas6 and Protein S (Fourgeaud et al., 2016 ). Importantly, microglial phagocytosis concurs with the upregulation of a unique neurogenic secretome (i.e., VGF, VEGF, FGF2), potentially suggesting a feedback loop for neurogenesis (Diaz‐Aparicio et al., 2020 ; Elmadany et al., 2020 ). Alternative to phagocytosis, hippocampal microglia contribute to neuronal cell death via CR3‐DAP12‐dependent production of superoxide ions (Wakselman et al., 2008 ).…”
Section: Understanding How Microglia Impact Neuronal Homeostasis and Functionmentioning
confidence: 99%
“…Hrh 2 (and also P2ry12 ) receptors are known to be linked to cAMP signaling pathways, and not‐like Hrh1 ‐ to Ca 2+ . However, it has been previously observed that GPCRs linked to G i or G s proteins can also elicit intracellular Ca 2+ elevations (Elmadany, de Almeida Sassi, et al, 2020; Kuhn et al, 2004; Pannell et al, 2014), potentially by signaling of the Gßɤ subunits in a PLC/IP 3 R‐dependent fashion from internal stores (Clapham, 2007). Ca 2+ elevations downstream of Hrh2 (Esbenshade et al, 2003) or P2ry12 (De Simone et al, 2010; Irino et al, 2008; Jiang et al, 2017; Pausch et al, 2004) activation were previously demonstrated.…”
Section: Discussionmentioning
confidence: 99%